New europium complexes and their use in red light-emitting diodes and vapoluminescent sensors. Issue 3 (3rd July 2021) - Devi, Rachna; Boddula, Rajamouli; Singh, Kasturi; Kumar, Satendra; Vaidyanathan, Sivakumar
Abstract : Three novel trivalent europium [Eu(III)] complexes – Eu(DBM)3 Phen-Ph-Ph, Eu(DBM)3 Phen-mCF3 -Ph, and Eu(DBM)3 Phen-pCF3 -Ph – were designed, synthesized, and characterized using various spectroscopic methods. Then their photophysical characteristics were investigated. The Eu complexes in the solid phase showed a pure red emission (due to the electric dipole transitions of the Eu 3+ ion). In a solution, they had multiple emissions due to their ligand contribution. The solvatochromism studies revealed that the Eu(III) complexes in the methanol and DMSO solutions had both metal ion and ligand emissions with similar intensities, which yielded a white emission. Of all the Eu(III) complexes, Eu(DBM)3 Phen-mCF3 -Ph showed the best quantum yield. In addition, the fluorinated mCF3 ligand had an unusually high lifetime value. Its remarkable linear decrease in luminescence intensity with increasing temperature opens a new window for its use as a sensitive temperature sensor at the 30–80°C range. The CIE color coordinates of the fabricated red LEDs (InGaN) are very close to the standard NTSC CIE color coordinates for bright red emissions, and the color purity as well as the LER values of the fabricated red LEDs are also very good. The Eu(III) complexes exhibited on-off photoluminescence switching via the vapoluminescent process and responded best to the acid-base (HCl-NH3 ) vapors. All these features suggest that the synthesized Eu(III) complexes are efficient candidates for red-emitting LEDs and vapoluminescent sensors. Organic chromophores, which are phenanthro-imidazole ligands based on fluorinated moieties coordinated with Eu(III) metal ions, very efficiently facilitate energy transfer from the ligand to the Eu(III) ion. The CIE color coordinates of the complexes showed a bright pure red emission, with x = 0.66 and y = 0.33 (612 nm). The fabricated light-emitting diode (LED) showed superior color quality and the complexes showed on-off-on luminescence behavior after exposure to the acid-base vapors.